Do conditional cash transfers increase schooling among adolescents? - Eric Draeger (International Economics and Economic Policy, 2021)
In several Latin American countries, conditional cash transfer programmes are a proven means of alleviating poverty in the short term and promoting education of children from disadvantaged families in the longer run. While the effectiveness of the Brazilian Bolsa Família for children's education outcomes up to 15 years of age has been widely documented, its contribution to the promotion of students of secondary school age has not been fully explored in light of the programme's expansion to 16-17 years olds in 2008. In this paper, I draw on Brazilian National Household Sample Survey data and use a difference-in-differences approach already applied in research in the context of Bolsa Família extension. Whereas these data were previously examined to detect intent-to-treat (ITT) effects due to insufficient information on treatment status, in this study I rely on a classifier method to additionally estimate average treatment effects on the treated who belong to families supposedly receiving Bolsa Família cash transfers. The results suggest that school attendance rates for 16-year-olds are particularly increased in the Brazilian Northeast, although the estimates are not significant when further time periods are taken into account. As comparably poor but non-recipient households have larger and consistently significant gains of school attendance, the effect on adolescent's education directly caused by the expansion of Bolsa Família remains ambiguous and thus cast doubt on the specific parallel trend assumption. In addition, no long-run ITT effects of the programme's expansion on school participation among 16 year old teenagers are found.
Keywords: 330; Bolsa familia; Conditional cash transfer programmes; Impact assessment; Difference-in-differences; Disadvantaged youth; Education